Characteristics of the Dual Board‐Certified Sleep Otolaryngology Workforce. (3rd July 2021) - Yu, Phoebe K.; Gadkaree, Shekhar K.; Li, Joanna; McCarty, Justin C.; Huyett, Phillip; Bergmark, Regan W.
Abstract : Objective: Sleep medicine is a multidisciplinary field that includes otolaryngology. After 2011, sleep medicine board eligibility required completion of a dedicated sleep medicine fellowship. The objective of our study is to describe the characteristics and geographic distribution of the dual board‐certified sleep otolaryngology workforce and to assess the impact of the 2011 change. Methods: A cross‐sectional analysis of sleep‐certified otolaryngologists registered with the American Board of Otolaryngology‐Head and Neck Surgery in 2019 was performed to characterize the sleep otolaryngology workforce. County and regional analysis of provider density was conducted by comparing provider characteristics with county‐level data from the United States Census Bureau. Results: There were 275 active dual board‐certified sleep otolaryngologists, or approximately 1 for every 1.12 million Americans. 77.8% were in private practice and 2.9% had American Society of Pediatric Otolaryngology membership. Eighty‐eight percent were male, with females more likely than males to be in an academic setting (36.4% for females compared to 20.2% for males; P  = .045). The South Atlantic and South Central regions had the highest number of sleep board‐certified otolaryngologists per capita. Before 2011, an average of 75.7 otolaryngologists took the sleep board exam per 2‐year cycle, compared to 14.3 otolaryngologists after 2011 ( P  = .029). Conclusion: There are few dual board‐certified sleep otolaryngologists across the country, which may affect care for patients with sleep‐disordered breathing. Increased resident exposure and otolaryngology training in sleep medicine can strengthen the otolaryngology contribution to the multidisciplinary care of these patients. Level of Evidence: 4 Laryngoscope, 131:E2712–E2717, 2021